Design methodology to enhance high impedance surfaces performances - Grelier, M.; Lepage, A. C.; Begaud, X.; Jousset, M.; Mallégol, S. (Advanced Electromagnetics, 2014)
A methodology is introduced for designing wideband, compact and ultra-thin high impedance surfaces (HIS). A parametric study is carried out to examine the effect of the periodicity on the electromagnetic properties of an HIS. This approach allows designers to reach the best trade-off for HIS performances.